Pengaruh Latihan Ladder Drill terhadap Kecepatan dan Kelincahan Atlet Bola Tangan Bojonegoro - Indra Dwi Purdianto; Gigih Siantoro (Journal on Education, 2024)
This study aims to determine the effect of ladder drill training on the speed and agility of handball athletes. This research method uses a type of quantitative research with a quasi-experimental method with a One Control Pretest-Posttest design. In this study there was a total sample of 20 handball athletes and was divided into 2 groups, 1. Experimental group, 2. Control group. The instruments in this study used the 30 meter Sprint Test and the Illinois Agility Test. Normality testing using the Shapiro-Wilk test, homogeneity testing using Levene-Test and for data analysis using the Paired Sample T-Test test. The results of this study indicate that handball athletes who do training using ladder drill tools experience increased speed and agility. This study concludes that there is a significant effect of ladder drill training on the speed and agility of handball athletes. So, this ladder drill training method can be recommended to handball coaches as a new way to increase the speed and agility of athletes.